2009
DOI: 10.1897/08-111.1
|View full text |Cite
|
Sign up to set email alerts
|

17α‐Ethinylestradiol alters reproductive behaviors, circulating hormones, and sexual morphology in male fathead minnows (Pimephales promelas)

Abstract: Ecologically relevant indicators of endocrine disruption in fish must be linked with measures of reproductive success. The ability of male fathead minnows (Pimephales promelas) to compete for, maintain, and defend a spawning substrate is paramount to reproductive success. The present study quantified alterations in male fathead minnow reproductive behaviors after exposure to environmentally relevant concentrations (0, 10, 20, or 40 ng/L) of 17alpha-ethinylestradiol (EE2) for 21 d. A video-based behavioral quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 58 publications
5
49
2
1
Order By: Relevance
“…In male goldfish, Martyniuk et al (2006) observed a significant 10-fold reduction in plasma E 2 and a 3-fold decrease in plasma T after 2 weeks exposure to 30 ng EE 2 /L. Male FHMs treated with 10, 20 or 40 ng EE 2 /L for 21 days showed significant decreases in E 2 , T, and 11-ketotestosterone of approximately 2-fold, 4-fold, and 10-fold respectively (Salierno and Kane, 2009). The relatively rapid inhibition of sex steroids by EE 2 has also been observed in female zebrafish ( Danio rerio ).…”
Section: Discussionmentioning
confidence: 99%
“…In male goldfish, Martyniuk et al (2006) observed a significant 10-fold reduction in plasma E 2 and a 3-fold decrease in plasma T after 2 weeks exposure to 30 ng EE 2 /L. Male FHMs treated with 10, 20 or 40 ng EE 2 /L for 21 days showed significant decreases in E 2 , T, and 11-ketotestosterone of approximately 2-fold, 4-fold, and 10-fold respectively (Salierno and Kane, 2009). The relatively rapid inhibition of sex steroids by EE 2 has also been observed in female zebrafish ( Danio rerio ).…”
Section: Discussionmentioning
confidence: 99%
“…The qPCR was performed using BioRad C1000 Touch Thermal Cycler, CFX96 Real-Time System, with the oligonucleotide primers Vtg2 5′-GGTGACTGGAAGAT CCAAG-′3 and Vtg2 3′-TCATGCGGCATTGGCTGG-′5 (Fernandez-Galaz et al, 1997). The samples were normalized against the mRNA expression of the housekeeping gene 18 s RNA (18a small ribosomal unit RNA) as internal reference, using the following primers: 18s 5′-AATGTCTGCCCTATCAACTTTC-′3 and 18s 3′-TGGATGTGGTAGCCGT TTC′5 (Salierno and Kane, 2009). All primer sets were tested for specificity and qPCR was performed using iTaq Universal Sybr Green Supermix (BioRad) according to the program previously described by ReyhanianCaspillo et al (2014).…”
Section: Vtg Gene Expression Analysismentioning
confidence: 99%
“…The fate of pharmaceutical effluents in aquatic environments is increasingly eliciting scientific inquiry owing to recent findings of their effects in biological systems [1]. Nigeria has a few pharmaceutical companies most of which are situated in Ogun and Lagos States in the country's south western region, discharging effluents into neighbouring rivers, creeks, and lagoons.…”
Section: Introductionmentioning
confidence: 99%